Effect of Health Education Intervention about Emergencies on the Knowledge and Ability of Parents in Handling Children with Emergency Condition - Ni Luh Putu Inca Buntari Agustini (Journal of Global Pharma Technology, 2016)
Introduction: Emergency is an unexpected and often dangerous situation requiring immediate action, accurate, and correct action to save lives. Delays in conducting emergency assistance often occur in children, adults and the elderly, where the consequences of the delay are permanent disability and even death. Emergency for children becomes an important concern because children are not used to expressing uncomfortable conditions in an emergency condition. Emergency conditions which often occur in children are febrile convulsion, choking and cardiac arrest. The purpose of this study was to identify the differences in parents’ knowledge before and after given education about febrile convulsion, choking, and cardiac resuscitation. Method: This research employed Pre-Experiment with One Group Pre-test Post-test design. The sample of this research was 70 parents who have children under five years. The sampling technique was used total sampling technique. Univariate analysis was used to determine the demographic data of respondents. Bivariate analysis was used to determine the differences in parents’ knowledge before and after given the education. Results: The research revealed that (Febrile convulsion P 0,000 <a = 0.05), (Choking P 0,000 <a = 0, 05), and (Cardiac arrest P 0.000 <a = 0.05). Conclusion: There is an effect of giving education toward parents' knowledge in handling children with emergency conditions. It is recommended that further activities and training on emergencies should be carried out steadily since emergencies can occur anywhere. So, it is important for parents to know the right guidance.Keywords: Emergency, Health education, Febrile seizures, Choking, Cardiac arrest.